Investigation of Optimal Allocation of Wind DG in Distribution System - Yadav, Kavita (Thapar University, Patiala, 2016)
Distributed Generation (DG) has gained more importance to meet the increased load demand. Its integration in a distribution system in comparison to conventional system stacks numerous potential benefits related to losses reduction, improvement in voltage profile, etc. Some of the issues of distributed generation is its rating, technology, sizing, siting, mode of operation, penetration level, etc. The thesis focuses on one of the issue that is optimal allocation of DG unit as the placement of dg unit at non-optimal places leads to increase in system loss and reduction in bus voltage profile. Alternative sources of energy based distributed generation has one of the considerable benefit as environmental friendliness. Hence, allocation of distributed generation units in proper place is an important aspect for maximizing the benefits stated above. Analysis of distribution network using power flow study plays an important role in the power system. The optimal location of wind based dg unit is determined using newton raphson method for obtaining the voltage profile with the analytical approach. The analytical expression used are based on exact loss formula. The proposed methodology has been tested and validated on IEEE 14 bus and 33 bus distribution systems. Results are obtained for normal load and with the increased load. The outcomes shows that by proper placement of wind based dg unit at relevant bus location the real power losses are minimized and corresponding bus voltages are improved.
ME Dissertation of Kavita Yadav (ME Power Systems) submitted to Electrical & Instrumentation Engg Dept at Thapar Univ Patiala
Keywords: distribution, wind, allocation, DG, Newton Raphson, IEEE